ANALISIS FINANSIAL USAHA PERIKANAN YANG BERBEDA PEMASARANNYA - Tampubolon, Dewi Murni; Ahmad, Muchtar; Nurmatias, Nurmatias (Fakultas Perikanan dan Kelautan Universitas Riau, 2011)
Financial analysis of the artisanal fishery by fish catch marketingdifferences done in Bagan Serdang village, North Sumatra, using survey methodsin data collecting. Fishermen, whose fish-catch market in the government managefish landing place and in the private fish landing place were interviewed. Financialanalysis result shows that yearly income of fishing that market their catch at thegovernment fish landing place earn Rp6,045,000 in average, while at the privateone earn only Rp2,600,000 (t-observe = 3.10 > t-tabel 0,01 = 2.42), thus verysignificance in income difference due to its distinction market pattern. All fishingshow efficient, as BCR > 1 and PPC less than 1.5 years. Eventhough, most of thefishers prefer to market their fish-catch at private landing place, mainly because ofreciprocity, better service and governance in the private landing place, beside‘patron-client’ relationship, in spite of its exploitative in their traditionalrelationship but tight attachment and dependency of fishermen to the individualowner of private landing place.